Guided tissue organization and disease modeling in a kidney tubule array. (November 2018) - Subramanian, Balajikarthick; Kaya, Oguzhan; Pollak, Martin R.; Yao, Gang; Zhou, Jing
Abstract: Three-dimensional (3D) in vitro kidney tubule models have either largely relied on the self-morphogenetic properties of the mammalian cells or used an engineered microfluidic platform with a monolayer of cells cultured on an extracellular matrix (ECM) protein coated porous membrane. These systems are used to understand critical processes during kidney development and transport properties of renal tubules. However, high variability and lack of kidney tubule-relevant geometries among engineered structures limit their utility in disease research and pre-clinical drug testing. Here, we report a novel bioengineered guided kidney tubule (gKT) array system that incorporates in vivo -like physicochemical cues in 3D culture to reproducibly generate homogeneous kidney tubules. The system utilizes a unique 3D micro-molded ECM platform in human physiology-scale dimensions (50-μm diameter) and relevant shapes to guide cells towards formation of mature tubule structures. The guided kidney tubules in our array system display enhanced tubule homogeneity with in vivo -like structural and functional features as evaluated by marker protein localization and epithelial transport analysis. Furthermore, the response of gKT structures to forskolin treatment exhibits characteristic tissue transformations from tubules to expanding cysts. Moreover, acute cisplatin injury causes induction of Kidney Injury Molecule-1 (KIM-1) expression as well as tubular necrosis and apoptosis. Thus the gKT array system offers enhanced structural uniformity with accurate in vivo -like tissue architecture, and will have broad applications in kidney tubule disease pathophysiology (including ciliopathies and drug-induced acute kidney injury), and will enhance pre-clinical drug screening studies. Graphical abstract: Image 1 Highlights: In vitro system supporting organotypic homogenous kidney tubule formation. Matrix combination, Micro pattern features, and Cells intrinsic properties act as determinants of final tissue outcomes. Exhibits characteristic kidney disease transformations in vitro . Scalable to high throughput configuration for drug testing applications.